(untitled) (PANGEEA, 2025)
The Aiud Valley tourist facility proposal describes Rimetea–Cheile Vălişoarei as the future resort along the Aiud Valley between Rimetea and Cheile Vălişoarei. It emphasizes the environmental and ethnographic values of the area (including Rimetea in UNESCO patrimony) and historic sites in Colţeşti, proposing cultural, durable tourism rather than mass tourism, with controlled development to avoid stress on nature and monuments.